Cyanoremediation and phyconanotechnology: cyanobacteria for metal biosorption toward a circular economy - Ciani, Matilde; Adessi, Alessandra (Frontiers in Microbiology, 2023)
Cyanobacteria are widespread phototrophic microorganisms that represent a promising biotechnological tool to satisfy current sustainability and circularity requirements. They are potential bio-factories of a wide range of compounds that can be exploited in several fields including bioremediation and nanotechnology sectors. This article aims to illustrate the most recent trends in the use of cyanobacteria for the bioremoval (i.e., cyanoremediation) of heavy metals and metal recovery and reuse. Heavy metal biosorption by cyanobacteria can be combined with the consecutive valorization of the obtained metal-organic materials to get added-value compounds, including metal nanoparticles, opening the field of phyconanotechnology. It is thus possible that the use of combined approaches could increase the environmental and economic feasibility of cyanobacteria-based processes, promoting the transition toward a circular economy.